Estado del arte de proyectos de agua potable y saneamiento básico con inversión pública y construcción de paz (2018)
drinking water and basic sanitation in these municipalities. A technical analysis is carried out on the projects presented in the Single Window of the Ministry of Housing, City, and Territory - Vice Ministry of Water and Basic Sanitation, referring to urban aqueducts and sewage systems in those municipalities, of which the management of the entities was analyzed. that have interference in the design, the allocation of resources, the contracting of the works, the execution and the control over them until the completion of the works, the operation and administration of the systems intervened, which entailed the analysis of the companies service providers in order to establish tools that generate alternatives and solutions to the various problems presented in them, in order to assess the real social and environmental impact of public investment in improving the quality of life of its inhabitants and the consolidation of peace in these territories.